2006
DOI: 10.1017/s0012162206002155
|View full text |Cite
|
Sign up to set email alerts
|

Palatal tremor in childhood: clinical and therapeutic considerations

Abstract: Palatal tremor (PT) is a rhythmic movement of the soft palate that often causes an ear click. PT can be symptomatic (SPT) or essential (EPT). The symptomatic form usually occurs in adults and the essential form mainly occurs in children. Several different treatments for EPT in children appear in the literature with variable reported efficacy. This report details four paediatric patients with EPT (three males, one female; mean age 6y 4mo [SD 6mo]; age at onset 6-7y) treated with piracetam (2-oxo-1-pyrrolidine a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 32 publications
0
7
0
5
Order By: Relevance
“…Due to an increased frequency of episodes of agitation, chlorpromazine therapy was started, then carbolithium was added, resulting in an improvement of the behavioral disturbances. Treatment with piracetam, the effectiveness of which in essential palatal tremor was recently reported by Campistol-Plana et al,3 was ineffective. It was not possible to administer treatment with botulinum toxin due to the patient’s limited cooperation.…”
Section: Case Reportmentioning
confidence: 90%
“…Due to an increased frequency of episodes of agitation, chlorpromazine therapy was started, then carbolithium was added, resulting in an improvement of the behavioral disturbances. Treatment with piracetam, the effectiveness of which in essential palatal tremor was recently reported by Campistol-Plana et al,3 was ineffective. It was not possible to administer treatment with botulinum toxin due to the patient’s limited cooperation.…”
Section: Case Reportmentioning
confidence: 90%
“…Campistol-Plana et al [14] suggested that TPV and tubal pharynx muscles are controlled by the glossopharyngeal nerve and pharyngeal plexus. Their treatment of four pediatric patients with 2% lidocaine resulted in the gradual disappearance of palatal tremors.…”
Section: Discussionmentioning
confidence: 99%
“…The pharmacological treatment for PT includes a variety of agents such as anticonvulsants, benzodiazepines, anticholinergic agents, calcium channel blockers (flunarizine), 5-hydroxytryptamine (5HT) and 5HT agonists (sumatriptan), nootropics (piracetam), placebos and botulinum toxin [17]. Tonsillectomy and other local therapies [7], relaxation techniques, voluntary mechanisms [17] such as the Valsalva maneuver, and dental devices [18] have also been attempted.…”
Section: Discussionmentioning
confidence: 99%
“…Tonsillectomy and other local therapies [7], relaxation techniques, voluntary mechanisms [17] such as the Valsalva maneuver, and dental devices [18] have also been attempted. However, the response of patients to these interventions is varied.…”
Section: Discussionmentioning
confidence: 99%